Spatial analysis of modern shop office floor plate in Malaysia - Awang, Arita Hanim; Denan, Zuraini (WMIT Group Sdn. Bhd, 2017)
Shop Offices usually have been the first option for companies to rent due to the low rental and maintenance criteria, however the limited spaces of shop offices to occupy a lot of office space requirements creates more challenge and problems to the tenants in terms of space planning and flexibility. In Malaysia, the layout of shop offices followed shop houses characters which are long and narrow with limited window opening. Problem arises as very minimal studies had been done to understand the typology of modern shop office design in Malaysia. The objective of this chapter is first to identify the floor plate shapes of modern shop office building typology in Malaysia and secondly to analyse the identified floor plate in terms of connectivity and integration values. Data was collected through a primary data collections of various sources namely from existing layout plan from the developers, online sources and field measurements and were analyzed using Axial Map and Visual Graph Analysis (VGA) of DepthmapX Space Syntax Software. The scope of this research is specialized to shop offices building typology in Kuala Lumpur only. This study is expected to provide a comparative analysis of the various designs of shop offices and to suggest the best criteria and attributes of the shop office typology that can benefits authorities, developers, as well as future tenants in choosing the suitable shop office layout to, accommodates their various need.